Indoor Gardening System (IGS) based Learning - Jamallullail, Muhammad Yusrin; Hakam Singh, Noppharat; Mohd Zaki, Nur Firzana; Bujang, Nur Mawarnie Alia; Saon , Sharifah; Mahamad , Abd Kadir (Evolution of Information, Communication and Computing System, 2022)
Agriculture is the practice of growing plants and raising animals for food, human needed or economic gain using art and science. It can be divided into two categories which are crop farming and livestock farming. Therefore, this project focusing on the life gardening system. There are many importance of plants for human and ecosystem. One of them is they produce food to organisms including human [1]. They also establish the atmosphere during process of photosynthesis and for sure the living can’t live without plants.